Effects of a multi-level intervention on hookah smoking frequency and duration among Iranian adolescents and adults: an application of socio-ecological model - Fatemeh Bakhtari Aghdam; Nader Alizadeh; Haidar Nadrian; Christoph Augner; Asghar Mohammadpoorasl (BMC, 2021)
Abstract Background The present study aimed to investigate the effects of a multi-level intervention on hookah smoking frequency and duration among Iranian adolescents and adults. Methods In this study, two comparable cities in Iran were selected to participate in an intervention program based on a social-ecological model (SEM). In each city, 133 hookah smokers in coffee houses were selected. Environmental changes in coffee houses such as serving light foods and games were conducted. A virtual group named "no hookah" was established on the Telegram application to train participants in the intervention group. Messages, pictures, and short videos were sent to the participants through that virtual network. The frequency and duration of hookah consumption were assessed in both groups at baseline and after the intervention. Results The frequency of hookah consumption decreased in 72.6% of participants in the intervention group (vs. 6.3% in the control group), and the duration of hookah consumption per session decreased in 39.5% of participants in the intervention group (vs. 5.5% in the control group). Conclusions Using multi-level interventions through a social-ecological model can reduce hookah consumption in adults.